THE EFFECTIVENESS OF USING THE RECIPROCAL TEACHING STRATEGY IN MATHEMATICAL THINKING FOR SECOND-YEAR INTERMEDIATE STUDENTS IN MATHEMATICS - Assistant Lecturer. Luma Ali Ahmeed Al-Agaili (European Journal of Humanities and Educational Advancements, 2023)
The study aimed to measure the effectiveness of using the reciprocal teaching strategy in mathematical thinking for second-year intermediate students in mathematics, the researcher followed the quasi-experimental method with the post-test . The study sample consisted of (42) students who were divided into two groups (Experimental and it’ number (21) students taught using the reciprocal teaching strategy, and control and its number (21) students. Students were taught in the usual way, and the two groups were equivalent on the extraneous variables. The researcher prepared two tests of mathematical thinking, consisting of (38) items, and validity, reliability, and statistical analysis of the items were conducted. One of the results of the research was the superiority of the experimental group that used the reciprocal teaching strategy .On the control group in mathematical thinking